Is acupuncture effective in treatment of hot flashes? - Woźniak, Piotr; Ziółkowski, Paweł; Stetkiewicz, Tomasz; Pięta-Dolińska, Agnieszka; Oszukowski, Przemysław (Menopause Review/Przegląd Menopauzalny, 2012)
The menopause is a successive stage of the woman’s life, during which the quality of her life decreases very frequently due to the occurrence of many diseases and symptoms, among others, the perimenopausal symptoms such as hot flashes. Hot flashes and hidrosis as their night equivalent, appear during the perimenopausal period in the majority of women. At the same time, they are the most frequent reason of women patients in the perimenopausal period, for seeing the gynaecologist. The basic therapeutic method used in treatment of the above mentioned disorders is the menopausal hormone therapy (MHT). Nevertheless, not every woman can apply the MHT, and some women are also afraid of using any hormone therapy. Namely, this group of women is looking for an alternative way to relieve symptoms of the climacteric. One of these methods is acupuncture, which gained a recognition within the last decade as a safe and effective method. The authors conducted a retrospective study with a group of 86 women patients in the perimenopausal period with the exacerbated vasomotor symptoms, who were not applying any MHT, but who underwent acupuncture treatment in 2010-2011. The study was to answer a question about effectiveness of acupuncture in treatment of hot flashes.